Role of the Basolateral Na+/H+ Exchanger-2 (NHE2) in Ionocytes of Seawater- Acclimated Medaka (Oryzias latipes) - Liu, Sian-Tai; Horng, Jiun-Lin; Lin, Li-Yih (Frontiers in Physiology, 2022)
Ionocytes in the skin and gills of seawater (SW) fishes are responsible for acid-base regulation and salt secretion. Na+/H+ exchangers (NHEs) are considered the major acid (H+)-secreting transporters in ionocytes of SW fishes. However, the subcellular localization and function of a specific NHE isoform (NHE2) have never clearly been revealed. In this study, we cloned and sequenced NHE2 from an SW-acclimated medaka (Oryzias latipes) and examined its functions in medaka embryos. A phylogenetic analysis showed that the evolutionary relationships of mammalian NHE2 and NHE4 are close to those of fish NHE2. A gene structure analysis showed that tetrapod NHE4 might be a tandem duplication of fish NHE2. Immunohistochemistry with a medaka-specific antibody localized NHE2 to the basolateral membrane of ionocytes. Lost-of-function experiments with photo-activated morpholino oligonucleotides showed that both H+ and Cl– secretion by ionocytes were suppressed in NHE2-knockdown embryos, suggesting that the basolateral NHE2 facilitates acid and salt secretion by ionocytes of medaka in seawater.